Students’ Perceptions of Intercultural Learning in English Language Learning - Sariwati Muhamad; Vebiyanti Nasir (PT. Anagata Sembagi Education, 2026)
Globalization demands the mastery of foreign languages integrated with an understanding of the speakers’ culture to avoid communication misunderstandings. This study aims to identify students’ perceptions, the influencing factors, and the impacts of cross-cultural learning in English language learning. This research uses a descriptive qualitative approach conducted at SMA Negeri 5 Tidore Kepulauan, involving 10 tenth-grade students selected through purposive sampling. Data were collected through semi-structured interviews, non-participant observation, and documentation, and analyzed using the interactive model of Miles and Huberman, which includes data reduction, data display, and conclusion drawing. The results show that students have a highly positive perception of cross-cultural learning. Cultural materials are considered to enhance global insight, increase learning motivation, and create more varied learning experiences. The main influencing factors include teachers’ teaching methods, material relevance, and the use of concrete examples. The impacts include improved intercultural communicative competence, an attitude of tolerance, and greater awareness of cultural diversity. In conclusion, the integration of cultural elements in English language learning plays an important role in supporting students’ academic and social competence in the global era.